Recent Advances in Biomedical, Therapeutic and Pharmaceutical Applications of Microbial Surfactants - Chiara Ceresa; Letizia Fracchia; Emanuele Fedeli; Chiara Porta; Ibrahim M. Banat (MDPI AG, 2021)
The spread of antimicrobial-resistant pathogens typically existing in biofilm formation and the recent COVID-19 pandemic, although unrelated phenomena, have demonstrated the urgent need for methods to combat such increasing threats. New avenues of research for natural molecules with desirable properties to alleviate this situation have, therefore, been expanding. Biosurfactants comprise a group of unique and varied amphiphilic molecules of microbial origin capable of interacting with lipidic membranes/components of microorganisms and altering their physicochemical properties. These features have encouraged closer investigations of these microbial metabolites as new pharmaceutics with potential applications in clinical, hygiene and therapeutic fields. Mounting evidence has indicated that biosurfactants have antimicrobial, antibiofilm, antiviral, immunomodulatory and antiproliferative activities that are exploitable in new anticancer treatments and wound healing applications. Some biosurfactants have already been approved for use in clinical, food and environmental fields, while others are currently under investigation and development as antimicrobials or adjuvants to antibiotics for microbial suppression and biofilm eradication strategies. Moreover, due to the COVID-19 pandemic, biosurfactants are now being explored as an alternative to current products or procedures for effective cleaning and handwash formulations, antiviral plastic and fabric surface coating agents for shields and masks. In addition, biosurfactants have shown promise as drug delivery systems and in the medicinal relief of symptoms associated with SARS-CoV-2 acute respiratory distress syndrome.